침 시술 이후 발생한 경추 척수 손상 - 우영하(Young-Ha Woo); 이지민(Ji-Min Lee); 심대무(Dae-Moo Shim); 배혁(Hyuk Bae) (The journal of the Korean Orthopaedic Association, 2020)
침술은 치료적 목적으로 신체의 특정부위에 바늘을 삽입하는 시술로 근골격계 질환의 증상 완화 목적으로 대중적으로 행해지는술기이다. 침술 이후 심각한 합병증은 20만 예 중 1예 가량으로 발생률이 낮고 대부분의 경우 증상이 가볍고 일시적이므로 비교적안전하다. 하지만 신경계 손상, 감염, 혈종, 폐기종 등 심각한 합병증이 발생할 수 있다. 저자들은 침술 이후 발생한 경추 척수 손상을 유발한 1예를 경험하였기에 이를 문헌 고찰과 함께 보고하는 바이다. Acupuncture, which is a procedure of inserting needles in a specific portion of the body to control pain, is conducted widely. The procedure is considered relatively safe because of its minimal side effects and low occurrence (1 in 200,000). On the other hand, its side effects include neurological damage, infection, hematoma, emphysema, etc . The authors report a case of cervical neurological damage that occurred after an acupuncture procedure. KCI Citation Count: 1